“5G Technology in the Digital Transformation of Healthcare, a Systematic Review“ - Cabanillas-Carbonell, Michael (2023)
“The world is currently facing one of the biggest problems related to health and the quality of healthcare. According to the goals outlined by WHO in the blueprint for sustainable development (SDG3), one of its objectives is to achieve universal health coverage and ensure a healthy lifestyle. In this regard, it is important to monitor and track the impact of applications that help address this problem. This systematic review provides an analysis of the impact of the 5G network on the use of apps to improve healthcare. An analysis of 343 articles was performed, obtaining 66 relevant articles, the articles were categorized into research conducted with fiber optic backbone network as well as future research. The main medical applications were identified as: telesurgery, mobile ultrasound, biosensor technology, robotic surgery and connected ambulance. In addition, it is classified and answer questions such as the most used to improve medical care and health quality, 5G-based applications used in media to improve medical care and health quality, databases and programming languages in telemedicine are the most used in 5G-based applications, the functionality available for telemedicine based on the use of 5G-based applications.“